2013
DOI: 10.1021/ac303586n
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quantification Using Resonance Energy Transfer between Donor Nanoparticles and Acceptor Quantum Dots

Abstract: A homogeneous time-resolved luminescence resonance energy transfer (TR-LRET) assay has been developed to quantify proteins. The competitive assay is based on resonance energy transfer (RET) between two luminescent nanosized particles. Polystyrene nanoparticles loaded with Eu(3+) chelates (EuNPs) act as donors, while protein-coated quantum dots (QDs), either CdSe/ZnS emitting at 655 nm (QD655-strep) or CdSeTe/ZnS with emission wavelength at 705 nm (QD705-strep), are acceptors. In the absence of analyte protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Quantum dots (QDs) are novel semiconductor nanocrystals with unique optical properties, including size-tunable photoluminescence spectra and relatively high quantum yield, and have been widely used as fluorescent markers in biological labeling, fluorescence imaging, and drug delivery [38,39,40,41]. In particular, QDs hold great promise as fluorescence resonance energy transfer (FRET) donors in the biosensing applications to homogeneously detect nucleic acids, proteins, and small molecules [42].…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Quantum dots (QDs) are novel semiconductor nanocrystals with unique optical properties, including size-tunable photoluminescence spectra and relatively high quantum yield, and have been widely used as fluorescent markers in biological labeling, fluorescence imaging, and drug delivery [38,39,40,41]. In particular, QDs hold great promise as fluorescence resonance energy transfer (FRET) donors in the biosensing applications to homogeneously detect nucleic acids, proteins, and small molecules [42].…”
Section: Quantum Dotsmentioning
confidence: 99%
“…The DCM has already proven its potential in multiplexed lung cancer assays 33 and protein concentration assays. 6 The method allows enhancing signal-to-background ratio. Therefore, very small changes in FRET signal can be extracted from luminescence decays with improved precision and, consequently, lower LODs can be achieved.…”
Section: Pccp Papermentioning
confidence: 99%
“…Their potential has already been demonstrated in drug screening assays, 1 luminescent cellular imaging, 2 homogenous 3 and heterogeneous 4 immunoassays, FRET fluoroassays 5 or in bioassays to determine protein concentration. 6 Typically, an LLC contains an organic chelate, central lanthanide ion, and optionally, a molecular spacer terminated with a functional group. The organic chelate acts as an ''antenna'' that first harvests and then transfers light to the central lanthanide ion (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, validation of FRET and consequent use of the formulism for the estimation of the molecular distance between the donor and the acceptor demands a careful analysis of the excited state lifetime of the fluorophores with picosecond resolution [12]. In some of the recent studies the usefulness of the picosecond resolved fluorescence measurement for the FRET based sensor (not using an optical fiber) has been recognized [13][14][15]. In a report using quantum dots linked to DNA have been used in an ultrasensitive nanosensor based on fluorescence resonance energy transfer (FRET) capable of detecting low concentrations of DNA in a separation-free format [13].…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that fluorescence lifetime data accurately be recorded via miniature fiber endoscopes that can discriminate dichotomous labeled structures and cells [14]. In a recent study FRET between donor nanoparticle and acceptor quantum dots is utilized in protein quantification [15].…”
Section: Introductionmentioning
confidence: 99%